Answer:
x = 3, y = 1 is the solution of the given system.
Step-by-step explanation:
Here, the given system of equations is:
y = -x + 4 ...... (1)
y = x - 2 .......... (2)
Now, to find the solution of the system, SUBSTITUTE the value of y from equation (1) in to the equation (2). We get ,
y = x - 2 ⇒ -x + 4 = x - 2 ( as from (1), y = -x + 4)
or, -x -x = -2 -4
or, - 2 x = -6 ⇒ x = 6/2 = 3
or, x = 3
⇒ y = x - 2 = 3 - 2 = 1
⇒ y = 1
Hence, x = 3, y = 1 is the solution of the given system.
The answer of this question is B
Answer:
multiply 3 by 2 and add 1 to get 7
Step-by-step explanation:
3x2+1=7
Answer:
71.58
Step-by-step explanation:
Answer:
12
Step-by-step explanation:
When you a coin flips there are 2 possible outcomes which are either heads, or tailer, when you roll a die there are six outcomes, one to six. Putting these together means you have a total of 2×6=12 outcomes